Attitudes toward biodiversity conservation of mangroves among coastal dwellers in Catanduanes - Masagca, Jimmy T. (Animo Repository, 1999)
The island province of Catanduanes in the Bicol Region has only about 1,735 ha of classified mangrove area (approximately 1.6% of the total mangrove area of the Philippines or 16% of the mangrove areal extent in Luzon.) Although the mangrove area is relatively smaller compared to other island provinces in the country, it has enormous significance on the ecology and economy of this typhoon-prone province.Current studies indicate that there are at least 20 major and minor mangal elements found in the mangrove areas which are characterized by both riverine and wave-dominating allochthonous materials. It appears the diversity of the mangrove vascular flora and macrofauna associated with this coastal marine ecosystem have long been subjected to stresses, i.e., typhoons, tidal surges and anthropogenic factors. Recently, there is now an increasing interest to involve the local people in various mangrove reforestation projects.The purpose of this paper is to provide a small contribution to mangrove research by examining the attitudes of coastal dwellers, specially teachers towards biodiversity conservation of mangroves. An understanding of their attitudes about the values of conserving mangroves will aid in formulating appropriate educational initiatives to encourage sustainable use, rational management, and biodiversity conservation. We hope to provide a case example which will stimulate further research on the socio-cultural factors related to success in mangrove reforestation or regeneration projects.